Reconstruction of Filarial Penis and Scrotum - Sharma, Dr. L. K. (Indian Journal of Plastic Surgery, 1972)
Eight cases of mild to severe degrees of elephantiasis scrotum and pents have been treated. The procedure followed in the present series was total - excision of the penile skin and free skin graft. Reduction of the scrotum by excising all the discased subcutaneous tissue and reconstruction of the scrotum by by scrotal flaps. The cosmatic and functional results have been presented. This procedure to reduce the size of scrotum and penis is most practical to relieve the patient from the great social embarrassment.